Karakteristik Pasacapanen Buah Manggis pada Berbagai Jenis Kemasan - Muakkada, Muhammad; Rahayu, Arifah; Ramdani, Hisworo (JURNAL AGRONIDA, 2016)
Packaging in horticultural products is done to maintain pysical and physiological quality and makedistribution and marketing easier to do, especially when it is combined with storage at low temperature.This study was aimed at assessing postharvest characteristics of mangosteen (Garcinia mangostana L.)fruits which were package in various packaging (scrap paper, Na-metabisuphide plastic, and combination ofscrap paper and Na-metabisuphide plastic) and stored at temperatures of 12oC and 28-29oC. Results showedthat storage at 12oC was better at maintaining weight, diameter, skin color (value a and value b), sepalcolor (value b), and TSS (total soluble solids) content. At 12oC, scrap paper packaging was able tomaintainskin color (value a), Na-metabisuphide plastic was able maintain skin color (value a), and thecombination of scrap paper and Na-metabisuphide plastic) was able maintain skin color (value L and b).Key words: low temperature, scrap paper, Na-metabisuphide plastic, mangosteen